Hubungan Sentimen Fad Diet dan Persepsi Citra Tubuh dengan Status Gizi Remaja di Surabaya: The Relationship between Fad Diet Sentiments and Body Image Perceptions with the Nutritional Status of Adolescents in Surabaya - Rahmawati, Anisah Firdausi; Arini, Shintia Yunita; Atmaka, Dominikus Raditya; Kusuma, Ardyanisa Raihan; Putri, Sheila Amara; Wijanarko, Mutiara Arsya; Nor, Norfezah Md; Shahid, Nadiatul Syima Mohd (Universitas Airlangga, 2025)
Background: Adolescence is an important stage of growth and development due to its ability to affect eating behaviours, which are likely to have an impact on a person's nutritional status. Objectives: This study aims to analyze the relationship between fad diet sentiments and body image perceptions associated with the nutritional status (BMI/A or Body Mass Index–for-age) of adolescents in Senior High School of 5 Surabaya. Methods: The research method employed a cross-sectional design with a sample size of 91 respondents selected through simple random sampling. Data collection of fad diet, body image, and nutritional status was conducted through questionnaire instruments, interviews, and anthropometric measurements. Data were analyzed using Pearson correlation and Fisher Exact's tests. Results: The results of this study indicate that 51.6% of respondents have overweight or obesity status. 46.2% of adolescents at Senior High School of 5 Surabaya have a negative body image, with the majority feeling dissatisfied with their weight and facial appearance. Based on statistical analysis results, there is a significant relationship between fad diet sentiment (p-value<0.05 and body image (p-value<0.05) with nutritional status (BMI-for-age). Conclusions: The conclusion drawn from this study is that the majority of respondents engage in fad diets by reducing meal frequency and 46.1% have negative body image perceptions.